Reorientasi Paradigma Education for All (EFA) di Era Digital - Laely Rizki Maulida; Devi Purwanti; Kharisma Yusuf Khairunnisa (Advances In Education Journal, 2026)
This study examines the relevance of the EFA paradigm to the process of transforming the education system in the 21st century.The issues raised are the extent to which EFA values ​​related to access, inclusion, and quality are still relevant and how they should be reformulated to address the demands of digital literacy, 21st-century competencies, and technological inequality. The study aims to describe the conceptual relationship between EFA and modern educational transformation and to formulate evidence-based policy directions. The method used is a systematic literature review of national and international scientific articles indexed by Scopus and SINTA. The study results indicate that EFA remains a normative foundation for educational equity, but needs to be reoriented from merely equal physical access to equal digital competencies and access. The findings highlight the importance of strengthening digital literacy, developing equitable digital infrastructure, developing teacher capacity for digital pedagogy, and affirmative policies to close the digital divide.